Tolerance and Natural Law - Budziszewski, J. (Revue générale de droit, 1998)
Although the practice of tolerance might appear to be endangered by the natural law, closer consideration shows that it is grounded in the natural law. By analysis we find that tolerance is a virtue of the Aristotelian type, founded on the two great pillars of right judgment in the protection of greater ends against lesser ends, and right judgment in the protection of ends against mistaken means, with the second being the more fundamental. While this analysis is new, the insights that it elaborates are old, as can be seen through consideration of the four different ways in which the medieval natural law thinker Thomas Aguinas qualified the classical idea that the purpose of law is to make men good. We conclude that although the natural law does generate a doctrine of tolerance, it does not produce a liberal doctrine of tolerance. That is, it is not based on neutrality, skepticism, abstract subjective rights, or a harm principle, whether of the generic of the John Stuart Millian variety.